Biology, morphology and damage of the lesser Coconut weevil, Diocalandra frumenti (Coleoptera: Curculionidae) in southern Vietnam - Ung Nguyen; THI-HIEN NGUYEN; NGUYEN-QUOC-KHANH CHAU; VAN-VANG LE; VAN-HAI TRAN (Society for Indonesian Biodiversity, 2020)
Abstract. Nguyen HU, Nguyen TH, Chau NQK, Le VV, Tran VH. 2020. Biology, morphology and damage of the lesser coconut weevil, Diocalandra frumenti (Coleoptera: Curculionidae) in southern Vietnam. Biodiversitas 21: 4686-4694. The lesser coconut weevil, Diocalandra frumenti, is an emerging pest of coconut trees in Vietnam. To help develop control options for D. frumenti, this study investigated its morphological and biological characteristics, and quantified damage levels on coconut trees. Results from the study showed that attack by D. frumenti on coconut trees is correlated with characteristic damage symptoms (e.g., oozing sap) on all maturity stages of coconut fruits throughout the year (24.7% infestation), with higher damage levels on young fruits (57.6%). Results also showed that infestation levels on trees (58.9%), coconut bunches (19.4%), and fruits (7.77%) varied greatly. Adults have four different morphologies, but genetic study showed that they are all one species. The life cycle from egg to adult averaged 167± 34.3 days. The average development time for eggs, larvae, female pupae, male pupae, male adults, and female adults was 5.62 ± 0.62, 142.3 ± 34.3, 9.79 ± 0.86, 10.2 ± 1.26, 81.5 ± 34.7, and 81.8 ± 37.2 days, respectively. In conclusion, D. frumenti is an important pest in coconut trees with significant fluctuations in the duration of its development stages, and variation in shape, color, and size of the eggs, larvae, pupae, and adults. They can attack any coconut orchard and have harmful impacts on coconut trees, coconut bunches, and fruits throughout the year.